Creation of an Android-Based AM Futsal Field Rental Application Using Flutter and JS Node with Midtrans Integration as a Payment Gateway - Kusumarini, Cahyawati Diah; Avito, Rio Farhan (GLOBAL: Jurnal Lentera BITEP, 2025)
In the modern era, technology has facilitated various aspects of life, including in the sport of futsal, which often requires an optimal training ground. Currently, Futsal AM South Tangerang still uses manual methods for field bookings, resulting in inaccurate reports and limited access. To overcome this problem, this research aims to develop an Android-based futsal field rental application using Flutter and Node.js with Midtrans integration as a payment gateway. The research method used is SDLC (Software Development Life Cycle) with Waterfall model, including planning, analysis, design, implementation, and testing. The results show that the developed application improves the efficiency of the rental process, simplifies data management, and provides a better user experience through integrated features such as login, registration, and payment. Black box testing ensures that the application runs well and is reliable in handling various usage scenarios. This application is expected to simplify the futsal field rental process and overcome the obstacles faced by users and admins.